Interpreting and implementing the Long Term Athlete Development Model: English Swimming Coaches' Views on the (Swimming) LTAD in practice - Lang, M.; Light, R. (International Journal of Sports Science and Coaching, 2010)
The LTAD (Long Term Athlete Development) model has come to represent a sports-wide set of principles that significantly influences national sports policy in England. However, little is known about its impact on the ground. This study is concerned with how national sporting bodies have adapted the model to their specific requirements and how local interpretation and implementation of this is operationalized and delivered. Interpretation and implementation of the LTAD model used in English swimming was investigated through interviews with six elite and five non-elite swimming coaches in the north of England. While there were concerns with aspects of the Amateur Swimming Association (ASA) regulations governing competition for age-group swimmers, the major concern expressed by participants was with over-emphasizing volumes of training, leading to the neglect of technique.